Why Has Energy Efficiency Not Scaled-up in the Industrial and Commercial Sectors in Ukraine? An Empirical Analysis - Hochman, Gal; Timilsina, Govinda R. (World Bank, Washington, DC, 2014)
Improvement of energy efficiency is one of the main options to reduce energy demand and to reduce greenhouse gas emissions in Ukraine. However, large-scale deployment of energy efficient technologies has been constrained by several financial, technical, information, behavioral, and institutional barriers. This study assesses these barriers through a survey of 500 industrial and commercial firms throughout Ukraine. The results from the survey were used in a cumulative multi-logit model to understand the importance of the barriers. The analysis shows that financial barriers caused by high upfront costs of energy efficient technologies, higher costs of finance, and higher opportunity costs of energy efficiency investment are key barriers to the adoption of energy efficiency measures in Ukraine. Institutional barriers particularly lack government policies, which also contributes to the slow adoption of energy efficient technologies in the country. The results suggest targeted policy and credit enhancements could help trigger adoption of energy efficient measures. The empirical analysis shows strong inter-linkages among the barriers and finds heterogeneity between industrial and commercial sectors on the realization of the barriers.